Beyond Process: TQM Content and Firm Performance - Reed, Richard; Lemak, David J.; Montgomery, Joseph C. (Academy of Management Review, 1996)
Authors of the literature on total quality management (TQM) have been much more concerned with process than content. This article considers TQM in relation to firm orientation and identifies market advantage, product design efficiency, process efficiency, and product reliability as the key feature of its content. Performance expectations for TQM. In the form of Increased revenues, reduced costs, and their time lags, are addressed in the context of environmental uncertainty.